Impacts of trade on growth, distribution and the environment in forest communities - Angelsen, A. (1998)
This paper develops a microeconomic framework to assess how opening up for trade will affect the overall welfare and its distribution within a forest community, as well as the impact on the environment. Whereas trade will increase overall welfare, it usually creates both winners and losers. The increased scale of the activity caused by trade is likely to have negative impacts on the environment when viewed in isolation, but it may also shift resources away from destructive activities. The paper briefly presents some tentative conclusions based on fieldwork in Sumatra, Indonesia.